Skeletal and dentoalveolar effects of class II malocclusion treatment using bi-maxillary skeletal anchorage: a systematic review - Maged S. Alhammadi; Amal Abdulsalam A. Qasem; Aisha Mohammed S. Yamani; Rawan Duhduh A. Duhduh; Rahaf T. Alshahrani; Esam Halboub; Abeer A. Almashraqi (BMC, 2022)
Abstract Background The goal of this systematic review was to assess the available evidence regarding the skeletal and dentoalveolar effects of bi-maxillary skeletal anchorage devices (BMSADs) used in treating growing class II malocclusion patients. Methods A comprehensive search was conducted on PubMed, Scopus, Science Direct, Web of Science, Cochrane, and LILACS up to November 2021, which was augmented by a manual search. The studies included were clinical trials (RCTs) and/or follow-up observational studies (retrospective and prospective). The outcomes of interest were the skeletal, dentoalveolar, and occlusal treatment-induced changes obtained from pre- and post-cephalometric measurements. The risks of bias of the included studies were assessed using an assessment tool from previous publications. Results Out of 742 screened articles, only 4 were eligible and thus included in the qualitative synthesis. They showed a moderate overall risk of bias. The results are presented as mean changes in both the study and control groups. All studies reported retrusion of the maxillary base and advancement of the mandible (meaning reduced ANB angle). Three of the included studies reported an increase in the vertical jaw relation, which was contrary to what the fourth study reported. Three studies reported an increase in the maxillary incisors' inclination or position, while one study reported their retroclination. Proclination of the mandibular incisors happened in two studies, whereas the other two studies reported retroclination. The overjet was reduced in all included studies. Conclusion Apart from the protrusive effects on the mandible, retrusive effects on the maxilla, and the consequent reduction of the overjet, BMSADs results in inconsistent skeletal and dentoalveolar effects. However, the current evidence is limited due to the variability in the biomechanics of the intermaxillary components, type of anchorage, and comparable groups in the included studies. Further RCTs with more standardized methodologies are highly encouraged. Clinical relevance BMSADs (using miniscrews or miniplates on both jaws) induces more skeletal than dentoalveolar effects. However, this must be practiced with caution, based on the benefit to risk (surgical insertion) ratio, and the limited evidence available in hand so far. Registration The protocol for this systematic review was registered at the International Prospective Register of Systematic Reviews (PROSPERO, No.: CRD42020199601).